Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

solve each equation. check you solution.
(7t - 2) - (-3t + 1) = -3(1 - 3t)


Sagot :

(7t-2) - (-3t+1) = -3*(1-3t)
First distribute:
7t-2+3t-1 = -3+9t
Now get all the terms with 't' on the same side by subtracting/adding:
7t+3t-9t = -3+2+1
Combine the terms:
1t=0
t=0

Check:
Plug in 0 for t and see if both sides of the equation come out the same:
Does (7(0)-2) - (-3(0)+1) = -3(1-3(0))  ?
(-2) - (1) = -3(1)  ?
-3 = -3  ?
Yes! It works, so t=0! 
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.